2003
DOI: 10.1023/b:brat.0000032859.68959.76
|View full text |Cite
|
Sign up to set email alerts
|

Role of Soft Bone, CSF and Gray Matter in EEG Simulations

Abstract: Effects of soft skull bone, cerebrospinal fluid (CSF) and gray matter on scalp potentials were examined with highly heterogeneous finite element models of an adult male subject. These models were constructed from segmented T1 weighted magnetic resonance images. Models had voxel resolutions of 1x1x3.2 mm with a total of about 1.5 million voxels. The scalp potentials, due to a dipolar source in the motor cortex area, were computed with an adaptive finite element solver. It was found that the scalp potentials wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 11 publications
4
106
0
Order By: Relevance
“…First, because CSF is highly conductive, minute shifts in CSF concentration can cause substantial alterations in EEG signals (Ramon et al, 2006;Ramon et al, 2004;Wendel et al, 2008). Using upright and recumbent MRI scanners, findings demonstrated that intracranial CSF concentration decreased when sitting up compared with lying down (Alperin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, because CSF is highly conductive, minute shifts in CSF concentration can cause substantial alterations in EEG signals (Ramon et al, 2006;Ramon et al, 2004;Wendel et al, 2008). Using upright and recumbent MRI scanners, findings demonstrated that intracranial CSF concentration decreased when sitting up compared with lying down (Alperin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To construct a realistic volume conductor model requires segmentation of the different tissues within the head with special attention to the poorly conducting human skull and the highly conductive CSF (Hämäläinen and Sarvas, 1987;Cuffin, 1996;Roth et al, 1993;Huiskamp et al, 1999;Ramon et al, 2004).…”
Section: Registration and Segmentationmentioning
confidence: 99%
“…28 These have emphasized the role of accurate segmentation of the cerebrospinal fluid (CSF) and bone. 29 A detailed 3D 29 The electrical activity in the top portion of the brain, above the eye level, was simulated with 125 dipoles randomly located in different parts of the brain. The dipole intensity distribution was in the range of 0.0 to 0.4 mA meter with a uniform random distribution.…”
Section: Segmentation Of the Head Mri Data For Modelling Electrical Amentioning
confidence: 99%
“…The dipole intensity distribution was in the range of 0.0 to 0.4 mA meter with a uniform random distribution. An adaptive FEM solver, described in Ramon et al (2004), 29 and Schimpf et al (1998) 30 , was used to compute flux and potential distribution in the whole head model. 31 Figure 9 shows that the current flow pattern follows the anatomical tissue boundaries very accurately.…”
Section: Segmentation Of the Head Mri Data For Modelling Electrical Amentioning
confidence: 99%